Behavior of Per- and polyfluoroalkyl substances (PFAS) in Pilot-Scale vertical flow constructed wetlands treating landfill leachate - Lott, Dreyton J (Waste management (New York, N.Y.), 2023)
Copyright © 2023 Elsevier Ltd. All rights reserved.